Password based door lock system using PIC microcontroller / Mohamad Hairy Zulfahmy Rosli and Muhammad Syazwan Hamzah - Rosli, Mohamad Hairy Zulfahmy; Hamzah, Muhammad Syazwan (2015)
Security is a prime concern in our day-today life. Everyone wants to be as much secure as possible. As access control for doors forms a vital link in a security chain. The microcontroller based on Door locker is an access system that allow only authorized person to access restricted area. The system is fully controlled by the 8 bit microcontroller PIC16f887 which has 256 byte password is stored in t EEPROM so that we can change it any time. The system has a Keypad by which the password can be entered through it. Then the microcontroller compares the four-digit password with the number which is pre-programed if it is equal or same then the microcontroller will switch on the motor for the door and if we entered the wrong password, the microcontroller will switch off the motor for the door.